MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA MENGGUNAKAN MEDIA POWTOON DI KELAS IV SEKOLAH DASAR - Diren Agasi; Nur Azmi Alwi; Yulia Maulani (Program Studi PGSD FKIP Universitas Bung Hatta, 2021)
Improving learning outcomes in the learning process is very important to prove achievement in the learning process, to improve learning outcomes we can use various ways, one of which is to improve Indonesian language learning outcomes by using Powton media. The method used in this research is quasi-experimental, using two groups posttest only which is part of quantitative research. This study using two groups posttest only presents a form of research where when determining the control group and the experimental group, the selection is done randomly (Prasetyo & Jannah, 2011: 117). The results of this study areThe average obtained by the experimental group is already above the Minimum Completeness Criteria (KKM) of 70, with details of 7 students getting the highest score and 12 students getting standard scores, and 6 students getting scores below the KKM. Another thing for the control group is that the average grade obtained is still below the KKM score, with details of 3 students getting the highest score, 4 students getting standard scores, and 18 students getting scores below the KKM. From the results of this study, it can be concluded that the success of using this powtoon application as a learning medium for Indonesian language subjects on the character of the characters in the story can be seen from the average value of the class or experimental sample group which is above the average value of the KKM. Keywords:( Learning Outcomes, Powtoon Media, Indonesian Language)